Renovation of the Heart : Putting on the Character of Christ - Willard, Dallas (NavPress, 2012)
A high school student reared in a Christian home turns to drugs and alcohol. A woman tries to stop criticizing others—for ten years. A father knows he needs more patience with his children, but his efforts seem in vain. // What do these people have in common? They are all in desperate need of further renovation of the heart, of transformation of the spirit. But just what is this transformation? Author Dallas Willard explains that its ideal end is when "all of the essential parts of the human self are effectively organized around God, as they are restored and sustained by Him. Spiritual transformation in Christ is the process leading to that ideal end, and its result is love of God with all of the heart, soul, mind, and strength, and of the neighbor as oneself." // Although you may acknowledge this as the ideal, you may still wonder how to get there? Renovation of the Heart helps to answer that inquiry. It lays a foundation for understanding the ruin and restoration of humanity by discussing human nature and its components, how they operate, and how they are renewed. It describes common misunderstandings about our human nature and the discipleship process. Most important, it outlines the general pattern of personal transformation—not as a formula, but as a systematic process that we have the responsibility to undertake as intentional apprentices of Jesus. Only then will our transformation be accomplished, through interaction with the grace of God in Christ, the presence of the Holy Spirit, and spiritual treasures stored in the body of Christ. //We aren't born again to stay the way we are. But how many times have we looked around us in dismay at the lack of spiritual maturity in fellow believers? There's good news. You can experience significant growth in your Christian walk, shed sinful habits, and increasingly take on the character of Christ. Willard calls this "the transformation of the spirit"—a divine process that "brings every element in our being, working from inside out, into harmony with the will of God or the kingdom of God."